Creatine supplementation does not improve sprint performance in competitive swimmers - Mujika, I.; Chatard, J. C.; Lacoste, L.; Barale, F.; Geyssant, A. (Medicine & Science in Sports & Exercise, 1996)
This study was conducted to examine the effects of creatine (Cr) supplementation on sprint swimming performance and energy metabolism. Twenty highly trained swimmers (9 female, 11 male) were tested for blood ammonia and for blood lactate after the 25-, 50-, and 100-m performance in their best stroke on two occasions 7 d apart. After the first trial, subjects were evenly and randomly assigned to either a creatine (5 g creatine monohydrate 4 times per day for 5 d) or a placebo group (same dosage of a lactose placebo) in a double-blind research design. No significant differences in performance times were observed between trials. Post-exercise blood ammonia concentration decreased in the 50- and 100-m trials in the creatine group and in the 50-m trial in the placebo group. The supplementation period had no effect on post-exercise blood lactate. Therefore, creatine supplementation cannot be considered as an ergogenic aid for sprint performance in highly trained swimmers although adenine nucleotide degradation may be reduced during sprint exercise after 5 d of creatine ingestion.